(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the interpretation of human suffering, experiences, conflicts between the environment and the individual in the novel “People in the Heat.” Based on the painful experiences of the heroes of the novel, it turned out that the conflict between human and nature, the individual and society was truthfully illuminated, and these interpretations were theoretically comprehended.